INFORMATION ON THE RANGE AND PHYSICOCHEMICAL PROPERTIES OF GLOVES (Conference Zone, 2022)
In this scientific article,experimental work on chemical-mechanical,hygienic, aesthetic requirements of several types of gloves was conducted and familiarized.